2017
DOI: 10.18869/acadpub.jnms.4.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peer education on quality of life in heart failure patients: A randomized clinical trial

Abstract: Background and Purpose: Heart failure (HF) is a chronic, debilitating disease, and physical limitations and progressive symptoms of which associated with this condition can reduce quality of life (QOL). Patient education regarding heart HF is one of the main components of self-care. In this respect, peer education is significant in improving health and creating a learning environment. This study was performed to determine the effect of peer education on QOL in HF patients. Methods:In this quasi-experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the above study by Gul and Karadag [7], those individuals who cared for their own tracheostomy and who used oesophageal speech reported higher QoL. Mohammadi et al [39] assessed the effectiveness of a self-care training by video method and found that routine training for patient care to watch at home improved QoL (including physical, mental, and social aspects) for 80 tracheostomised patients, compared to those patients receiving only routine care training.…”
Section: Wellbeing and Quality Of Lifementioning
confidence: 99%
“…In the above study by Gul and Karadag [7], those individuals who cared for their own tracheostomy and who used oesophageal speech reported higher QoL. Mohammadi et al [39] assessed the effectiveness of a self-care training by video method and found that routine training for patient care to watch at home improved QoL (including physical, mental, and social aspects) for 80 tracheostomised patients, compared to those patients receiving only routine care training.…”
Section: Wellbeing and Quality Of Lifementioning
confidence: 99%
“…Following tracheostomy and discharge home, access to video resources led to increased quality of life scores. 29 Internet-published video is easy to reference when patients have nonemergent questions or concerns, and it can improve patients’ senses of agency over their health. Previous research has shown that implementing tracheostomy education programs for caregivers is effective as well.…”
Section: Implications For Practicementioning
confidence: 99%
“…Providing a supplemental resource can benefit only the patients. Following tracheostomy and discharge home, access to video resources led to increased quality of life scores 29 . Internet‐published video is easy to reference when patients have nonemergent questions or concerns, and it can improve patients’ senses of agency over their health.…”
Section: Implications For Practicementioning
confidence: 99%
“…For this reason, in planning the discharge of a person with a tracheostomy, the main objective is to ensure the recovery of autonomy for a safe return home and re-adaptation to the existing environment (Nicouleau & Cotto, 2015). Therefore, it is expected that the person acquires skills that enable stoma self-care and handling the tracheostomy devices, to ensure airway protection, prevent complications (Spito & Cavaliere, 2019) and enhance quality of life (Mohammadi et al, 2015). Thus, most nursing interventions for the person with a tracheostomy are focused on self-care.…”
Section: Introductionmentioning
confidence: 99%